Hydrodynamics of dense gas-solid fluidized beds with immersed vertical membranes using an endoscopic-laser PIV/DIA technique. (8th June 2018) - Helmi, A.; Campos Velarde, I.; Gallucci, F.; van Sint Annaland, M.
Graphical abstract: Highlights: Hydrodynamics of fluidized bed with vertically immersed membranes is investigated. The behavior of the fluidized bed is significantly influenced by the presence of the membranes. The degree of gas-solid mixing inside the bed may be decreased to a very large extent. Up to 3.5 times lower equivalent bubble diameter in comparison with the case without internals. Abstract: The hydrodynamic behavior of a bubbling gas-solid fluidized bed with vertically immersed membrane tubes has been studied using an endoscopic-laser PIV/DIA technique. The solids mass flux and hold-up profiles were determined together with the bubble phase properties (equivalent bubble diameter and bubble rise velocity) for different operating conditions and different membrane bundle configurations. The obtained results revealed that the lateral solids motion can be significantly hampered due to the presence of the membrane tubes resulting in a very high solids hold-up near the walls and much diluted regions in the middle of the bed. The obtained results from the experiments with a different number of membranes, membranes with a different outer diameter, and positioned with the bottom of the bundle at different axial positions in the bed, give guidelines to optimize the membrane configurations to achieve the highest lateral gas dispersion and optimal bubble breakage. These experimental results have also demonstrated the very important effect of tube spacers on the hydrodynamics. Moreover, the analysis of the bubble phase properties confirmed the enormous decrease in equivalent bubble diameter (up to a factor 3.5) for fluidized beds with immersed vertical membranes with spacers in comparison with a fluidized bed without internals, showing the great potential for improvement of the bubble-to-emulsion phase mass transfer rate. This work has been selected by the Editors as a Featured Cover Article for this issue.